Evaluating Awareness of Pediatricians and General Practitioners on Transformation of the Health System in Iran - Sepideh Masoud; Gilda Rajabi; Farnaz Delavari; Nima Rezaei (Acta Medica Iranica, 2017)
In orders to promote the level of healthcare in societies, governments try to have different policies to transform the health system. The aim of this study was to measure the level of awareness of practitioners in Iran, after initiating the new transformation of the health system in the country, starting from May 2014. This is a descriptive–cross-sectional study, which was inducted in October 2014. The study population consists of 208 physicians who attended the 26th International Congress of Pediatrics in Tehran, Iran. Data was collected using a self-structured questionnaire, which was estimated as both reliable and valid. Two hundred and eight questionnaires were returned. The results showed that 79.1% of the practitioners were aware of the new health system. Indeed 48.3% of the participants believed that the system was successful. 57.7% of physicians were completely aware of the time of the new system settlement in the country, while the rest had either no idea or did not know the exact date. The participants suggested a few items promote the health system in the country; among them, decreasing the direct payment between patients and physicians was suggested most frequently. According to the results obtained from the study, it is suggested that health care administrators have a detailed plan for health care workers prior to settlement of a new health policy installment, in order to succeed in settlement of a program.